Analysis of the Relationship Between Digital Marketing Strategies and Customer Orientation with the Competitive Advantage of SMEs - Icin Quraysin; Ngadino Surip Diposumartob; Hari Muharam (Department of Tadris IPS FITK UIN Siber Syekh Nurjati Cirebon, 2024)
MSMEs in Banten tend to have marketing strategies that are less flexible in facing market changes. The rapid development of digital technology and increasingly complex consumer behavior requires a new marketing approach. To overcome this problem, this research examined how digital marketing and market orientation can influence the competitive advantage of MSMEs in Banten. This research used a quantitative approach with a population of 3.174 MSME enterprises engaged in KBLI-10 or the food industry in Banten Province. Through multistage sampling with purposive sampling and proportional random sampling methods, 347 MSME actors were identified as respondents in this study. Data were collected using a survey/questionnaire method and analyzed using simple and multiple linear regression. The results showed that digital marketing and market orientation positively and significantly affected competitive advantage, both partially and simultaneously. Therefore, this research implies that the more MSMEs focus on increasing digital marketing efforts and market orientation, the greater the opportunity to improve the competitive advantage of MSMEs in Banten Province.Keywords: Digital Marketing; Market Orientation; MSMEs (Micro, Small, and Medium Enterprises).